Perbedaan Kemampuan Literasi Sains dengan Menggunakan Pembelajaran Kooperatif Tipe Jigsaw dan Group Investigation - Yena Harnita; Tomi Hidayat; Apriza Fitriani (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aims to describe students' scientific literacy skills in Biology learning through the application of cooperative learning models: Jigsaw, Group Investigation, and conventional methods. The method used was an experimental study with a posttest-only control group design. The results showed that there was no significant difference in scientific literacy skills among Grade X students of SMA Negeri 9 Kaur across the three learning models, based on ANOVA and LSD tests with a significance level of α > 0.05. The average scores of students’ scientific literacy were Jigsaw class = 35, Group Investigation class = 34.091, and conventional class = 30.909. In conclusion, the application of Jigsaw, Group Investigation, and conventional learning models did not result in a significant difference in students’ scientific literacy skills.   Keywords: Scientific Literacy Skills, Biology Learning